Improved subsurface mapping by enhancing resistivity horizontal resolution - M. M., Nordiana; Rosli, S.; M. Nawawi, M. N.; I., N. Azwin; I. N. E., Hidayah; Z. A. M., Hazreek; A. B., Andy; M., Saidin (2012)
Geotechnical studies are usually used for subsurface, engineering and environmental works. Geophysical study provides supported data in order to save cost and time. The survey was executed to solve engineering problems and environment. Geophysical methods can be used to determine depth of bedrock, thickness of soils, near surface structure such as fault and cavity. A resistivity study is another method of mapping shallow subsurface and become increasingly more widespread in their use. In this paper, resistivity technique will be developing in order to get detail and deeper penetration in shallow subsurface study. By enhancing resistivity horizontal resolution to establish targets, most of the required information can be mapped and the results verified, thus improving the subsurface mapping of the engineering and environmental works. This technique is called as EHR (Enhancing Horizontal Resolution). EHR technique is applied at two sites, miniature model and real site. From the results, EHR technique improves the horizontal changes in subsurface resistivity